The Correlation Between Financial Literacy and Microcredit Access on The Profitability of Horticular Farming Enterprises - Muhammad Zais M. Samiun (PT. Anagata Sembagi Education, 2025)
Horticultural farming plays a vital role in rural livelihoods and agricultural diversification, yet many smallholders struggle with low financial literacy and limited access to affordable credit, which constrains profitability. This study investigates the correlation between financial literacy and microcredit access on the profitability of horticultural farming enterprises. Using a quantitative correlational design, primary data were collected from 200 horticultural farmers through structured questionnaires covering financial literacy indicators, microcredit access, and profitability measures such as net profit margin, return on investment, and gross margin. The data were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression. The results show that financial literacy is strongly correlated with profitability (r = 0.63, p < 0.01), while microcredit access also exhibits a positive but weaker correlation (r = 0.42, p < 0.05). Regression analysis confirms both variables as significant predictors of profitability, with financial literacy (β = 0.46, p < 0.01) exerting greater influence compared to microcredit access (β = 0.28, p < 0.05). The model explains 51% of the variation in profitability, highlighting that credit provision alone is insufficient without adequate financial capability. This study concludes that financial literacy and microcredit access act as complementary enablers of farm profitability. Strengthening financial education alongside inclusive microcredit programs is therefore essential to enhance the sustainability and competitiveness of horticultural enterprises.